Sensation of Anteroposterior and Lateral Body Tilt Induced by Electrical Stimulation of Ankle Tendons - Takahashi, Nozomi; Amemiya, Tomohiro; Narumi, Takuji; Kuzuoka, Hideaki; Hirose, Michitaka; Aoyama, Kazuma (Frontiers in Virtual Reality, 2022)
While virtual reality technology enables users to walk on surfaces of various shapes in virtual environments, these experiences are often on a flat floor, and any discordance between visual and somatosensory information hampers the immersive experience. To resolve this issue, we have focused on the ankle joint angle as an essential cue in detecting the surface shape of the ground. To modulate the sensation of the ankle joint angle, we propose novel percutaneous electrical stimulation methods that stimulate four targeted ankle tendons: the tibialis anterior muscle tendon, the Achilles tendon, the peroneus longus muscle tendon, and the flexor digitorum longus tendon. Since electrically stimulating the elbow tendon is known to evoke reflexive hand movement, electrically stimulating the ankle tendon is expected to evoke a body tilt due to illusory changes in the ankle joint angle. In this study, we designed electrode configurations to stimulate the above four ankle tendons using a finite element analysis and investigated the effect of electrically stimulating the ankle tendons on the subjective sensation of body tilt and actual body sway through psychophysical experiments. The results revealed that applying this stimulation with our novel electrode configurations can induce a subjective sensation of body tilt and actual body sway in a direction opposite to the stimulated part.